(untitled) (Eurasian Research Bulletin, 2023)
It has been identified that the supplementary use of unconventional agro-minerals as additional nutrients in increasing soil fertility and enhancing the yield of crops is yielding favorable results in our Republic. Unconventional agro-minerals such as glauconite, phosphorite, and bentonite deposits in our country are rich in micro and macro elements. When added to the soil through various methods and means, they have proven to be beneficial to farmers and growers due to their cost-effectiveness and high efficiency. According to the data, Uzbekistan has more than 200 bentonite deposits with a total reserve exceeding 2 billion tons. It has been found that the use of bentonite and glauconite sands in various agricultural fields in countries like the USA, Italy, Czech Republic, Russia, and Ukraine can increase crop yields by 20-30%. Furthermore, the research regarding the impact of eye-catching, development, and productivity indicators on the eye, seeds, soil fertility, mineral nutrients, and the influence of organic matter has not been conducted, which is considered a gap in this subject matter.